2017
DOI: 10.4049/jimmunol.1700615
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Mucosal-Associated Invariant T Cells Induces CD40L-Dependent Maturation of Monocyte-Derived and Primary Dendritic Cells

Abstract: Mucosal-associated invariant T (MAIT) cells are innate T cells that recognize intermediates of the vitamin B2 biosynthetic pathway presented by the monomorphic MR1 molecule. It remains unclear whether, in addition to their cytolytic activity that is important in antimicrobial defense, MAIT cells have immune-modulatory functions that could enhance dendritic cell (DC) maturation. In this study, we investigated the molecular mechanisms dictating the interactions between human MAIT cells and DCs and demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 42 publications
(49 reference statements)
5
110
0
Order By: Relevance
“…Besides production of cytokines and cytotoxic molecules that have direct effect on infection control, MAIT cells have role in immune regulation. It has been reported that MAIT cells drives the differentiation of inflammatory monocytes into monocyte‐derived DCs through early pulmonary GM‐CSF production during pulmonary intracellular infection and induces maturation of DCs via CD40L‐dependent pathway . It has been reported that MAIT cells promote plasmablasts of B cells and production of IgA, IgG and IgM .…”
Section: Discussionmentioning
confidence: 92%
“…Besides production of cytokines and cytotoxic molecules that have direct effect on infection control, MAIT cells have role in immune regulation. It has been reported that MAIT cells drives the differentiation of inflammatory monocytes into monocyte‐derived DCs through early pulmonary GM‐CSF production during pulmonary intracellular infection and induces maturation of DCs via CD40L‐dependent pathway . It has been reported that MAIT cells promote plasmablasts of B cells and production of IgA, IgG and IgM .…”
Section: Discussionmentioning
confidence: 92%
“…is detectable in a small proportion of PB MAIT cells, 43,46 but neither CD94 nor NKG2A is found on the CD4 + subset. 50 Importantly, when compared with their CD94 − , CD56 − , and CD84 − counterparts, MAIT cells expressing these molecules more readily produce IFNin response to IL-12 and IL-18.…”
Section: Mait Cell Surface Molecules Associated With Cytotoxicitymentioning
confidence: 89%
“…For instance, CD94, which associates with NKG2A, −C, −E, and −F to recognize the MHC class Ib molecule HLA‐E, is not uniformly expressed by all PB MAIT cells . Of note, NKG2A is detectable in a small proportion of PB MAIT cells, but neither CD94 nor NKG2A is found on the CD4 + subset . Importantly, when compared with their CD94 − , CD56 − , and CD84 − counterparts, MAIT cells expressing these molecules more readily produce IFN‐γ in response to IL‐12 and IL‐18 .…”
Section: Mait Cell Surface Molecules Associated With Cytotoxicitymentioning
confidence: 99%
See 2 more Smart Citations